Eurycomanone exerts antiproliferative activity via apoptosis upon MCF-7 cells - Cheah, Shiau Chuen; Pihie, Azimahtol Hawariah Lope (Penerbit Universiti Sains Malaysia, 2004)
E. longifolia Jack belongs to the Simaroubaceae family and is abundant in South East. From the roots of E. longifolia Jack, used as a folk medicine, a highly oxygenated quassinoid, named eurycomanone was isolated. Eurycomanone, a C20 quassinoid is a cytotoxic bioactive ingredient found in E.